(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Kobernik O. M. Project technology: application possibilities in education. In the article the essence of the teaching of design and technology project to identify common approaches to defining the stages of project, revealed the possibility of using technology in project of educational and training activities, the lessons of labor training and after school, in higher education teaching.